Nasogastric tube care and flushing in a Portuguese general medicine ward: a best practice implementation project. (11th September 2022) - Fernandes, António M.; Henriques, Pedro; Lourenço, Ana R.; Mateus, Fernando; Santos, Joana; Marques, Daniela; Apóstolo, João L.A.; Cardoso, Daniela F.B.; Klugar, Miloslav; Klugarová, Jitka
ABSTRACT: Objectives: To implement evidence-based practice related to care and flushing of nasogastric tubes inserted for feeding, in a general medicine ward. Introduction: Nasogastric tube feeding is a widely used nutritional support form. Although performed by qualified professionals, it is not a harm-free intervention. Progression to the trachea during initial insertion, aspiration of gastric contents, improper position for patient feeding, and/or a blocked tube are examples of problems that can occur. Methods: The project used JBI's methodological approach of the Clinical Evidence System and Getting Research into Practice audit and feedback tool. A baseline audit focused on nursing procedures related to the maintenance of nasogastric tube feeding, based on 14 criteria informed by the JBI evidence summaries, was performed for a month. Education sessions and other engagement strategies and resources were used to increase nasogastric tube maintenance. This best-practice implementation was conducted in Portugal, between January 2020 and April 2021, in a 33-bed general medicine ward with a staff of 30 registered nurses. Results: Different samples, for each audited procedure, were obtained from a universe of 25 nurses and 14 episodes of patients with nasogastric tube in baseline and 10 in follow-up audit. At baseline, compliance with the criteria ranged from 0 to 88%. Ten of the 14 criteria were below 50%. The follow-up audit showed significant improvement in all compliance criteria (ranging from 44.4 to 100%). Criteria 1 and 2, which were aimed at preventing adverse consequences related to wrong placement or displacement of the nasogastric tube, showed a high postimplementation compliance level (89.3 and 90%). Conclusion: With an integrated plan incorporating interventions, strategies, and resources, tailored for this context, we improved nurses' knowledge of nasogastric tube maintenance and achieved significantly increased compliance with nasogastric tube care best-practice. We suggest maintaining current strategies, and reinforcing clinical supervision and regular assessment.